The Prohibition of Usury in Islamic Economic Viewpoint - Samad, Telsy Fratama Dewi; Sugeng, Anggoro (Tapis: Jurnal Penelitian Ilmiah, 2022)
Usury is a praxis, which can cause economic disruption. Many intellectuals in the field of economics, philosophers, and religious experts have discussed this case globally. This study aims to describe the concept of Usury and how Islamic Economics view usury’s praxis, which will be described in this paper according to Quran and Hadith statements. The method used in this research is a qualitative method by conducting library research using books, journals, articles, the Holy Qur’an, and Sunnah as a source of references. The result found that Usury is prohibited in Islam because of the economic effect caused by usury praxis. There are many sources in the Quran and Hadith that can be used as references concerning the prohibition of Usury. Thus, it can be concluded that the Muslim people should follow and perform what had been stated in Quran as a guideline for living according to Islamic principles.